Dampak Model Pembelajaran Realistic Mathematics Education (RME) Terhadap Kemampuan Pemecahan Masalah Matematis Siswa Pada Materi Persamaan Garis Lurus Berbantuan Geogebra - Putri Solihat, Tifany Anggraeni; Roesdiana, Lessa; Haerudin, Haerudin (Polinomial : Jurnal Pendidikan Matematika, 2022)
This study aims to determine the impact of the Realistic Mathematics Education (RME) learning model on students' mathematical problem solving abilities on the material of straight line equations assisted by GeoGebra. Two classes have been determined to apply the RME (Realistic Mathematics Education) learning model with the help of GeoGebra and the conventional learning model without using GeoGebra. Furthermore, the sampling used purposive sampling method and two classes were selected in one of the junior high schools in Karawang Regency in class VIII F and VIII I. The results showed that the mathematical problem solving ability of students who were treated with the GeoGebra-assisted RME learning model was better than students who applied conventional learning models without the help of GeoGebra.